Cheetahs - Unwin, Cynthia (2019)
Did you know that while a cheetah can reach speeds of up to 60 mph (96.6 km/h) in just three seconds-it can also stay perfectly still for half an hour while hunting? This title offers a complete picture of the animal- from birth to adulthood- and describes its place in our world, including how humans impact it and its environment.
Includes index.
8-11
Keywords: Cheetah -- Juvenile literature